Enforcement of the Prosecutor's Dominus Litis Principle Against the Authority of Military Auditors as Public Prosecutors in Military Courts - Nurul Amaliah; M. Syukri Akub; Haeranah (Al-Risalah, 2022)
Enforcement of the Dominus Litis Principle of the Prosecutor's Office against the Authority of Military Prosecutors as Public Prosecutors in the Military Courts with the presence of UURI No. 31 of 1997 concerning Military Justice there is an overlap of authority with the principle of dominus litis from the prosecutor's office as the only state institution that is given authority in prosecution in Indonesia. This research is an empirical normative research, combining the normative legal approach of legislation with empirical elements in the form of interviews. The results showed that the authority possessed by military prosecutors as public prosecutors in military courts clashed with the dominus litis principle of the prosecutor's office as the only state institution granted authority in prosecutions in the country, but with the establishment of Jampidmil in the organizational body of the prosecutor's office specifically as a public prosecutor in the military courts, as a solution to restore the principle of dominus litis as a foundation ...